2006
DOI: 10.1111/j.1095-8649.2006.01143.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of external dummy transmitters on oxygen consumption and performance of swimming Atlantic cod

Abstract: Decreased critical swimming speed and increased oxygen consumption (M O2 ) was found for externally tagged Atlantic cod Gadus morhua swimming at a high speed of 0Á9 body length (total length, L T ) s À1 . No difference was found in the standard metabolic rate, indicating that the higher M O2 for tagged cod was due to drag force rather than increased costs to keep buoyancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 21 publications
3
21
2
Order By: Relevance
“…The study demonstrated a higher oxygen demand of tagged fish. A similar approach with small numbers of tagged and untagged cod showed a higher mass-specific oxygen consumption rate of tagged fish during swimming, indicating that there is a measurable drag effect from the tag [62], as predicted by Arnold and Holford [49]. In a study of the effect of external tagging on juvenile rainbow trout (Oncorhynchus mykiss), Lewis and Muntz [63] used tail beat frequency, opercular beat rate, and drag measurements as indicators of swimming performance.…”
Section: Swimming Performancementioning
confidence: 99%
“…The study demonstrated a higher oxygen demand of tagged fish. A similar approach with small numbers of tagged and untagged cod showed a higher mass-specific oxygen consumption rate of tagged fish during swimming, indicating that there is a measurable drag effect from the tag [62], as predicted by Arnold and Holford [49]. In a study of the effect of external tagging on juvenile rainbow trout (Oncorhynchus mykiss), Lewis and Muntz [63] used tail beat frequency, opercular beat rate, and drag measurements as indicators of swimming performance.…”
Section: Swimming Performancementioning
confidence: 99%
“…U opt values obtained from forced swimming experiments are often stated as being ecologically important, as fish are thought to swim close to optimum speeds during routine movements (Ware 1978;Webb 1991). However, discrepancies between the U opt value and the average routine swimming speed exist for species that are not primarily swimming steady and linear, for example, Atlantic cod (Gadus morhua; Bjo¨rnsson 1993;Schurmann and Steffensen 1994;Lo¨kkeborg and Ferno¨1999;Steinhausen et al 2006). This is in accordance with the lower U opt value observed in this study for spontaneous swimming seabream compared with the seabream that were forced to swim.…”
Section: Swimming Costs At U Optmentioning
confidence: 99%
“…Another method is to mount specific sensors on the fish with the purpose of measuring speed (Kawabe et al 2003(Kawabe et al , 2004, changes in speed (Freadman 1981;Clark et al 2010) or turnings. However, the number of invasive sensors should be limited as it may decrease the mobility and increase the energy demand on the fish (Steinhausen et al 2006;Gollock et al 2009). A single sensor measuring either the caudal differential pressure (Webber et al 2001;Steinhausen et al 2007;Gollock et al 2009) or the electromyogram of the working muscles (Cooke et al 2004) may be suitable methods.…”
Section: Estimating Spontaneous Swimming Costmentioning
confidence: 99%
“…Steinhausen et al (2006) reported that U crit decreased when a dummy tag of 37 g (~3% of body mass, BM) was externally attached to Atlantic cod. However, these authors only observed a significant effect of the tag on MO 2 at velocities greater than 0.79 BLÁs -1 and reported a decrease in U crit of 13% (untagged = 1.14 BLÁs -1 ; tagged = 0.99 BLÁs -1 ).…”
Section: (B) Comparison Of Maximum Oxygen Consumption Of Tagged (Solimentioning
confidence: 99%
“…In this study, we used DPT, with internally (intraperitoneally) implanted acoustic transmitters, to further evaluate the applicability of this technology for measuring the swimming speed and energetics of freeranging cod and to record the pattern of swimming activity of free-ranging cod in a large tank. These studies were important, as Steinhausen et al (2006) showed that placing the transmitter body of the DPT externally may increase swimming-related metabolism above 0.8 body lengths (BL)Ás -1 and decrease critical swimming speed (Steinhausen et al 2007). Further, we used ''hard-wired'' fish to examine the potential of two other physiological parameters for measuring cod swimming speed, and indirectly, oxygen consumption: (i) EMG, which has proven successful for quantifying the swimming activity of a number of freshwater fish species (Cooke et al 2004) and (ii) sonomicrometry, which measures changes in muscle length with each contraction.…”
Section: Introductionmentioning
confidence: 98%